2003
DOI: 10.1073/pnas.1733909100
|View full text |Cite
|
Sign up to set email alerts
|

A noncanonical sequence phosphorylated by casein kinase 1 in β-catenin may play a role in casein kinase 1 targeting of important signaling proteins

Abstract: Protein kinase casein kinase 1 (CK1) phosphorylates Ser-45 of ␤-catenin, ''priming'' the subsequent phosphorylation by glycogen synthase-3 of residues 41, 37, and 33. This concerted phosphorylation of ␤-catenin signals its degradation and prevents its function in triggering cell division. The sequence around Ser-45 does not conform to the canonical consensus for CK1 substrates, which prescribes either phosphoamino acids or acidic residues in position n؊3 from the target serine. However, the ␤-catenin sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 53 publications
7
115
0
Order By: Relevance
“…The spectral analysis revealed another doubly charged (2 þ ) signal at m/z 823.27, identified as the same 115-128 peptide that was modified with two phosphate groups at levels of both S122 and S125, with no modifications seen on S120. The phosphomodification on S122 occurs outside of the consensus sequence, a phenomenon that has been described for other casein kinase substrates (Marin et al, 1994(Marin et al, , 2003.…”
Section: Resultsmentioning
confidence: 68%
“…The spectral analysis revealed another doubly charged (2 þ ) signal at m/z 823.27, identified as the same 115-128 peptide that was modified with two phosphate groups at levels of both S122 and S125, with no modifications seen on S120. The phosphomodification on S122 occurs outside of the consensus sequence, a phenomenon that has been described for other casein kinase substrates (Marin et al, 1994(Marin et al, , 2003.…”
Section: Resultsmentioning
confidence: 68%
“…Hence, we decided to identify the specific kinases responsible for Tiam1 phosphorylation that led to ␤-TrCP recognition. Analysis of the amino acid sequence in Tiam1 revealed many serine and threonine residues coincident with CK1 consensus phosphorylation motifs, D/EXXS and S/T-PO 4 XXS/T (42). Therefore, we performed a coimmunoprecipitation assay and found that Tiam1 interacted predominantly with CK1␦ and CK1⑀, whereas its interaction with CK1␣ was much weaker and, with CK1␥, undetectable ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…CK1 initially phosphorylates Ser45 of b-catenin (Amit et al 2002;Liu et al 2002), and is targeted to this site by a cluster of acidic residues located seven amino acids carboxy-terminally ( Fig. 1) (Marin et al 2003). GSK-3 phosphorylates residues in the sequence S/T-X-X-X-pS/pT, in which the bold residue represents the phosphorylation site, and X is any amino acid (Fiol et al 1987;.…”
Section: Phosphorylation By the Destruction Complexmentioning
confidence: 99%